Synthesis of highly substituted 1,2-diazetidin-3-ones, small ring scaffolds for drug discovery - Santos, Marilla S.; Nortcliffe, Andrew; Lewis, William; Bradshaw, Tracey D; Moody, Christopher J. (Wiley-VCH Verlag, 2018)
1,2-Diazetidin-3-ones are readily accessible, small ring scaffolds that upon functionalization have the potential to produce diverse 3-dimensional structures for drug discovery. Thus treatment of diazo hydrazides, obtained from simple hydrazides and malonyl half ester derivatives, followed by diazo transfer, with catalytic amounts of rhodium (II) acetate dimer results in intramolecular carbenoid N–H insertion to give 1,2-diazetidin-3-ones. Although subsequent functionalization reactions could be hampered by the lability of the 4-membered ring, a wide range of new derivatives was available by deprotection at N-1, and subsequent amide or urea formation. The structures of four four-membered rings was confirmed by X-ray crystallography; the compounds showed modest growth inhibitory activity in mammary carcinoma cells.